2018
DOI: 10.2147/opth.s160758
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting visual outcomes after treatment of infectious endophthalmitis in northeastern Thailand

Abstract: ObjectiveTo determine factors affecting visual outcomes after treatment of infectious endophthalmitis during 2012–2016 at a large referral eye center in northeastern Thailand.Patients and methodsMedical charts of patients with a diagnosis of infectious endophthalmitis including demographic data, types of endophthalmitis, causative organisms, methods of treatment, anatomical, and functional outcomes were retrospectively reviewed. Factors associated with improved visual outcomes were analyzed.ResultsFour hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
4
11
1
Order By: Relevance
“…The results obtained for pathogenic bacteria were consistent with the findings of most reports [2,14,18,19]. We obtained anterior aqueous humor and or vitreous fluid for bacterial culture from 316 patients, and the culture-positive rate was 44.62%.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained for pathogenic bacteria were consistent with the findings of most reports [2,14,18,19]. We obtained anterior aqueous humor and or vitreous fluid for bacterial culture from 316 patients, and the culture-positive rate was 44.62%.…”
Section: Discussionsupporting
confidence: 90%
“…In our study 67.5% had total cataract which matches with other studies which had 74% total cataract. 9,10 In our study, BCVA of 6/18-6/6 was seen in 56% cases after surgical treatment, 6/36-6/24 in 24% cases and 8% cases had BCVA equal to or less than 6/60. Some studies achieved visual acuity of >6/18 after surgery, and suggested that the initial visual acuity and patient age were predictors.…”
Section: Discussionsupporting
confidence: 47%
“…Usually, EKPE patients are adults [8, 12, 23, 24]. Although the median age in our study was 51.3 years, the youngest patient in our case series was only 3 years old.…”
Section: Discussionmentioning
confidence: 61%